Improving students' ability to write narrative texts using pictures - Eliyawati Eliyawati (AL-ASASIYYA: Journal Of Basic Education, 2020)
This study is aimed in improving students' writing ability by using pictures in narrative text for Grade XI- IPS 5 SMA N 1 Cigugur Kuningan, the survey used of t-test data of experimental and control groups on pre-test and the shows that tactic is lower that ttab (0, 07 ˂ 1, 6759) that is no significant difference of pre-test mean of both groups.  The result of there are given a different treatment, and it means that there is a considerable difference in the post-test way of both groups, which is the post-test mean of the experimental group is significantly higher. The result t-test of a hypothesis test in the experimental group, whit is tactic ˃ tab or 9, 72 ˃ 1, 7081 so the alternative hypothesis (Ha) the researcher found that the students gave positive responses on the use of the picture on student narrative writing skill.  The results of the questionnaire analysis were only offered to the experimental group, which for the affective aspect was 370 or with the "agreed" criteria, for cognitive perspective are 170.  It indicates the students' feeling toward English subject commonly, writing activity, and writing narrative text using picture especially is good. For the behaviour is 273 or in the "strongly agree" criteria. It indicates using snapshot is very good, an idea or belief toward English is essential are excellent, and they also agreed toward the difficulties of writing text without any media. After using a picture in writing narrative activity, these conclude that picture is significantly improving student narrative writing skill, and It's they made a considerable improvement in some aspect of writing skills such as content, organization, vocabulary and grammar.